Financial Conditions Indexes for Asian Economies - Margarita Debuque-Gonzales; Maria Socorro Gochoco-Bautista (Asian Development Bank (ADB), 2013)
Financial conditions indexes (FCIs) are constructed for five Asian economies, namely, Hong Kong, China; Japan; the Republic of Korea; Malaysia; and Singapore, using a principal component analysis (PCA) methodology from Hatzius et al. (2010) and quarterly data. Various financial stress indicators are included, allowing the constructed Financial Condition Index to capture important episodes in each economy's financial history. The predictive power of the constructed FCIs is higher than that of benchmark AR models and they generally outperform single financial indicators. A decomposition of the FCIs sheds light on particular sources of financial stress. A regional FCI based on the individual economy FCIs is also constructed.
hdl:11540/2083
Keywords: E44; F37; G17; 330; financial conditions index; Asia; principal component analysis; Finanzsektor; Wirtschaftsindikator; Vergleich; Hongkong; China; Japan; Südkorea; Malaysia